Entrepreneurship and its impacts on the economy due to the Covid-19 pandemic - Hu Chan, Gidalti Abihail (Universidad Autónoma de Tamaulipas, 2021)
The objective of this work is to carry out an exhaustive analysis of theories about entrepreneurship and its impacts on economic activities due to the health crisis of the pandemic that is developing in the current world by COVID-19. That is why, in this review, some of these impacts are identified through documentary research. To carry out this research, various databases were used, such as; Scopus, Emerald, Redalyc, Ebsco, ResearchGate, Google Scholar, as well as to obtain more information when making this article, the data of the Economic Commission of Latin America and the Caribbean (ECLAC) was revised to complement and give greater truth. And finally, it concludes by way of reflection with some recommendations aimed at recently created ventures.